Penerapan Algoritma Saw Pada Sistem Penilaian Anggota Terbaik Ukm Granat - Alfiansyah, Rizky; Atika, Prima Dina; Fathurrozi, Ahmad (Universitas Dirgantara Marsekal Suryadarma, 2023)
The purpose of determining the best members is to appreciate the achievements of members so as to motivate other members to be able to organize optimally and be able to survive in the organization for a long time. Although the purpose is very simple. It turns out that the process is very complex, takes so long that it gives rise to the opportunity for errors to occur in determining who is the right member. Especially if the UKM GRANAT has members with an assessment that is not much different from other members, then in its determination it is sometimes very subjective. Actually, there are several assessment criteria in the decision-making process for selecting the best members, namely: attendance, activeness, responsibility, professionalism, initiative, behavior. Therefore, it is necessary to build a system that can help decision making to determine the selection process objectively, namely by using the SAW (Simple Additive Weighting) method.